ISBD for Manifestation: Single-Entity Cataloguing in a Multiple-Entity Bibliographic Universe - Dunsire, Gordon (Monografija u povodu 20 godina rada Odjela za informacijske znanosti u Zadru, 2025)
The paper describes issues that arise from a project to develop a metadata content standard for a single entity in a multiple-entity data environment. The ISBD for Manifestation project is an initial and partial implementation of an entity-relationship data model that identifies 10 distinct entities that are of interest in the bibliographic description of resources held in library and cultural heritage collections. The project focuses on one of the entities and aims to deliver a set of elements with associated guidance and stipulations that function in standalone applications while maintaining integration with a subsequent and full implementation of the model. The model is designed for Semantic Web technologies and linked open data, but partial implementation requires the use of relational data in local, closed applications. The paper discusses how the boundaries of distinct entities determine the operational data requirements of closed bibliographic universes within the open universe of all things, and describes several methods for incorporating descriptions of and references to instances of entities within and beyond the local universe. These methods include the specification of note elements that refer to external entities, of relationship and shortcut elements that cross entity boundaries, and of appellation elements that provide references across entity boundaries. The paper uses examples taken from the draft ISBD for Manifestation and the standards to which it is related.